The analysis of features of occurrence of inertial explosion in problems of high-speed impact of metal penetrators into the studied celestial body and meteor-technogenic particles into elements of spacecraft - E. V. Leun; D. B. Dobriza; А. А. Poliakov; V. К. Sysoev (Омский научный вестник: Серия "Авиационно-ракетное и энергетическое машиностроение")
The article discusses the features of the occurrence of an inertial explosion (IE) in the problems of high-speed impacts on a solid barrier of two types of impactors: metal penetrators into the studied celestial body for space contact scientific research and meteor-technogenic particles into the elements of spacecraft. The features of IE, the conditions of its occurrence and the results of theoretical and experimental studies are analyzed. The ratio of the calculated impact velocity, leading to the appearance of willows, to the speed of sound in different metals tending to a certain average value is discussed. The influence of contact and thermoelectric phenomena and the temperature of the impactor on the occurrence of IE, as well as its dependence on the cross-sectional area of the impactor, is discussed. The ways of preventing the occurrence of IE are considered.